Foreign exchange markets, behavior of options volatility and bid-ask spread around macroeconomic announcements - Muhammad Ishfaq; Muhammad Usman Arshad; Muhammad Kashif Durrani; Muhammad Saleem Ashraf; Ahmad Qammar (Cogent Economics & Finance, 2022)
The purpose of this study is to examine the role of options volatility and bid-ask spread as microstructural variables in determining whether the foreign exchange market's price formation process in response to macroeconomic announcements is characterised by changes in risk perception and transaction costs. The findings suggest that behavioural characteristics of market participants appear to trump macroeconomic considerations. The volatility indices and bid-ask spreads were found more sensitive to announcements than forex returns, which directly imply weak assimilation of common knowledge into exchange rates. The forex returns, bid-ask spread, and volatility indices demonstrated less vulnerability towards Chinese announcements than the USA, UK, Japan, and Euro. Moreover, findings distinctly signify the role of China as a global liquidity provider by reducing trading costs in the foreign exchange markets. The implications suggest that core macroeconomic models should incorporate agents' heterogeneous expectations based on risk perceptions than the order flow approach.
Keywords: E02; C58; F31; 330; Foreign exchange market; options volatility; macroeconomic announcements; VAR